Basic Soccer Skills: A Cross Sectional Study on Junior High School Students - Hasyim, Andi Hasriadi; Haris, Iyan; Ramadhan, Ramadhan (Indonesian Journal of Sport Management, 2023)
The level of mastery of basic soccer techniques of junior high school students has yet to be discovered. This study aims to determine how much mastery of basic soccer techniques of football students of SMP Negeri 1 Kolaka. Methods: The methodology used is a survey method with a cross-sectional type. The dribbling test has a mean value of 49.99 with a very poor category, namely as many as 18 students with a percentage of 45%; shooting tests with a mean value of 50.00 with a very poor category, namely as many as 21 students with a percentage of 52.5%, passing-control with a mean value of 50.00 with a very poor category, namely as many as 15 students with a percentage of 37.5%, and heading tests with a mean value of 50.00 with a very good category, namely as many as 17 students with a percentage of 42.5%. The mastery of basic soccer techniques of SMP Negeri 1 Kolaka students is an average value of 200.00, with a percentage value of 52.5% or as many as 21 students in the good category. Knowing the mastery of basic soccer techniques of students is used as a data bank to conduct further research.